Social Media Attachment: Developing a Formative, Multidimensional and Parsimonious Index - Baboo, Shabanaz; Nunkoo, Robin; Cock, Florian (Elsevier, 2022)
There is little consensus on the dimensions of social media attachment, conceptualized as a unidimensional construct by some scholars and multidimensional by others. The conceptual labels given to those dimensions also differ across studies, posing challenges to researchers. This study addresses some of those conceptual issues by developing a formative index of social media attachment. It employs a two-staged methodology involving interviews that are used to develop the items and elicit the dimensions of attachment and a survey to test the index empirically. The results provide support for an eight-item parsimonious index that captures the multifaceted nature of social media attachment: connecting/socializing; keeping up to date; dependence; dysfunctional use; expressing feelings; self-presentation; seeking self-esteem; and seeking knowledge. The index displays sound psychometric properties and is nomologically valid. Theoretically, it reflects the various conceptualizations of social media attachment in a single short measure. The index is also practically useful to researchers.